1977
DOI: 10.1002/app.1977.070210412
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behavior of isoprene polymers and butadiene polymers

Abstract: SynopsisThe oxidation behavior of cis-1,4-polyisoprene, emulsion polyisoprene, emulsion isoprenehtyrene copolymers, and emulsion butadienehtyrene copolymers by heat aging or ultraviolet irradiation has been investigated from the change of gel fraction and molecular weight distribution. It was determined that the oxidation behavior of both isoprene and butadiene polymers is strongly dependent on the composition of the polymers as well as on the microstructure of the polymers. In the case of oxidation by heat ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Thermal treatment of unvulcanized and vulcanized elastomers has been a field of significant research. [22][23][24][25][26] In a study by Colin et al, 22 trans-polyisoprene is shown to oxidize in atmosphere similar to the behavior observed here via mechanisms such as chain-scission and cross-linking. Using molecular dynamics simulations, Li et al 27 show that (sulfur) cross-linking leads to shrinkage of cis-polyisoprene chains.…”
Section: B Pre-heating Of Polyisoprene Filmssupporting
confidence: 79%
“…Thermal treatment of unvulcanized and vulcanized elastomers has been a field of significant research. [22][23][24][25][26] In a study by Colin et al, 22 trans-polyisoprene is shown to oxidize in atmosphere similar to the behavior observed here via mechanisms such as chain-scission and cross-linking. Using molecular dynamics simulations, Li et al 27 show that (sulfur) cross-linking leads to shrinkage of cis-polyisoprene chains.…”
Section: B Pre-heating Of Polyisoprene Filmssupporting
confidence: 79%